Studies on Life Processes: Hydration of the Microenvironment and Fungal Growth (Biological Sciences - PJSIR, 2022)
by hydration to saturation, immediately after removal from incubationat 25°, by soaking in water for 2 hrs. The excess waterwas removed by filtration and the hydrated straw, after weighing,was allowed to dehydrate at 25° for 24,48 and 72 hrs andthe dehydrated straw weighed again.